Meningkatkan Kemampuan Membaca Kata Melalui Model Scramble Bagi Anak Tunagrahita Ringan - Marsela, Tia; Zulmiyetri, Zulmiyetri; Damri, Damri (Jurnal Penelitian Pendidikan Khusus, 2022)
The background of this research is that there are two children withmild mental retardation in grade VII at SLB N Merlung who haveproblems with their ability to read words. The methods previouslyapplied were demonstrations, lectures and questions and answers inlearning to read words with individual assignments, for this reason theresearchers aimed to improve children's reading skills by using thescramble method.This type of research is classroom action research, where there aretwo cycles, each cycle consisting of four meetings. This research wasconducted with the collaboration between researchers and observers. .The data obtained from this study are through observation, action tests,and documentation. Data were analyzed qualitatively andquantitatively.The results showed that: 1) the process of learning to read wordsfor mentally retarded children was carried out using a scramble model.2) the ability to read words for mild mentally retarded children ingrade VII increases through the scramble model.